Cities, Crowding, and the Coronavirus : Predicting Contagion Risk Hotspots - Bhardwaj, Gaurav (World Bank, Washington, DC, 2020)
Today, over 4 billion people around the world—more than half the global population—live in cities. By 2050, with the urban population more than doubling its current size, nearly 7 of 10 people in the world will live in cities. Evidence from today's developed countries and rapidly emerging economies shows that urbanization and the development of cities is a source of dynamism that can lead to enhanced productivity. In fact, no country in the industrial age has ever achieved significant economic growth without urbanization. The underlying driver of this dynamism is the ability of cities to bring people together. Social and economic interactions are the hallmark of city life, making people more productive and often creating a vibrant market for innovations by entrepreneurs and investors. International evidence suggests that the elasticity of income per capita with respect to city population is between 3 percent and 8 percent (Rosenthal & Strange 2003). Each doubling of city size raises its productivity by 5 percent. But the coronavirus pandemic is now seriously limiting social interactions. With no vaccine available, prevention through containment and social distancing, along with frequent handwashing, appear to be, for now, the only viable strategies against the virus. The goal is to slow transmission and avoid overwhelming health systems that have finite resources. Hence non-essential businesses have been closed and social distancing measures, including lockdowns, are being applied in many countries. Will such measures defeat the virus in dense urban areas? In principle, yes. Wealthier people in dense neighborhoods can isolate themselves while having amenities and groceries delivered to them. Many can connect remotely to work, and some can even afford to live without working for a time. But poorer residents of crowded neighborhoods cannot afford such luxuries. They are forced to leave their home every day to go to work, buy groceries, and do laundry. This is especially true in low-income neighborhoods of developing countries – many of which are slums and informal settlements. In fact, 60 percent of Africa’s urban population is packed into slums - a far larger share than the average 34 percent seen in other developing countries (United Nations 2015). With people tightly packed together, the resulting crowding increases contagion risk from the coronavirus.